Adapting to climate change: snow load assessment of snow galleries on the Iron Ore Line in Northern Sweden - Saback, Vanessa; Gonzalez-Libreros, Jaime; Daescu, Cosmin; Popescu, Cosmin; Garmabaki, Amir Soleimani; Sas, Gabriel (Frontiers in Built Environment, 2024)
The snow galleries along the Iron Ore railway line in northern Sweden have facedproblems in recent years due to increasingly large snow loads, and several gallerieshave been damaged. These incidents motivated an evaluation of the maximumload supported by the galleries before collapse, which is presented in this study. In2021, a monitoring system was installed in one of the main frames of two snowgalleries built in the 1950s to follow up with temperature and displacements,including a trigger that sends out a warning message when a critical load isreached. A literature review on snow loads was performed, followed bycalculations on snow distribution on the galleries based on the Eurocodes andNational Swedish Standards. Finite element 2D and 3D models were created usingAxisVM to accurately assess the efforts in the structural elements. Analysis anddiscussion are complemented by observations from site visits. It was concludedthat the critical loads supported by the galleries are lower than the requirements oftoday’s standards, but since secondary construction elements were damagedbefore the main frames reached their full capacity, no major collapse has yet takenplace. The cobweb effect (load re-distribution between the neighboring elementsin a 3D structure) influenced the behavior of the galleries in the 3D analysis and thecapacity of the main frames proved to be significantly increased compared to the2D assessment. Validerad;2024;Nivå 1;2024-01-19 (signyg); Licens full text: CC BY 4.0